Intrarenal B Cell Cytokines Promote Transplant Fibrosis and Tubular Atrophy. Issue 12 (24th July 2015) - Tse, G. H.; Johnston, C. J. C.; Kluth, D.; Gray, M.; Gray, D.; Hughes, J.; Marson, L. P.
Abstract : Renal transplantation is the optimum treatment for end‐stage renal failure. B cells have been identified in chronic allograft damage (CAD) and associated with the development of tertiary lymphoid tissue within the human renal allograft. We performed renal transplantation in mice to model CAD and identified B cells forming tertiary lymphoid tissue with germinal centers. Intra‐allograft B220 + B cells comprised of IgM high CD23 − B cells, IgM lo CD23 + B cells, and IgM lo CD23 − B cells with elevated expression of CD86. Depletion of B cells with anti‐CD20 was associated with an improvement in CAD but only when administered after transplantation and not before. Isolated intra‐allograft B cells were cultured and shown to synthesize multiple cytokines, the most abundant of these were GRO‐α (CXCL1), RANTES (CCL5), IL‐6 and MCP‐1 (CCL2). Tubular loss was observed with T cell accumulation within the allograft and development of interstitial fibrosis, whilst type III collagen deposition was observed in areas of F4/80 + macrophages and PDGFR‐β + and transgelin + fibroblasts, all of which were reduced by B cell depletion. We have shown that intra‐allograft B cells are key mediators of CAD. B cells possibly contribute to CAD by intra‐allograft secretion of cytokines and chemokines. Abstract : In a mouse model of chronic renal allograft damage, B cells accumulate in the kidney and produce multiple inflammatory chemokines, and depletion of these B cells with anti‐CD20 reduces interstitial fibrosis and tubular atrophy.